(3CKQ GdbGfhf GdaQfSj Ydi GdbGfhf GdeUQj EHGf GdMedI GdaQfSjI Ydi eUQ (B/ s - (3SjO eZGhQj SjO YHO GdSdGes; (3Wg YhV ZGRj eMeOs; (3YHO GdgGOj ahRj eNJGQ GdYhVjs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI(B.s, 2021)
(3JfGhdJ GdOQGSI HMK GdNdGa Mhd eOi UMI hLhO CKQ ddbGfhf GdaQfSj Ydi GdbGfhf GdeUQj EHGf GdMedI GdaQfSjI Ydi eUQ, hPdc aj KdGKI CHhGH, JfGhd GdHGH GdJegjOj (B: (3OQGSI GdbGfhf GdeUQj bHjd GdMedI GdaQfSjI Ydi eUQ NdGd Mce GdeeGdjc hMce GdYKeGfjjf deUQ dJhVjM GdfXe GdbGfhfjI aj GdaJQI GdSGHbI Ydi bOhe LjT GdMedI GdaQfSjI; hJfGhd GdHGH GdChd GdaJQI GdJj JYGUQ hLhO LjT GdMedI GdaQfSjI aj eUQ, hJfGhd GdHGH GdKGfj GdaJQI GdJj HOCJ HLdGA LjT GdMedI GdYScQjI GdaQfSjI MJi fgGjI Mce CSQI eMeO Ydj; dCf GdMedI GdaQfSjI de JfJg ef GdfhGMj GdYdejI hGdKbGajI hGdacQjI ; hJfGhdJ GdOQGSI HMK GdfXe GdbGfhfjI aj cd ef aQfSG heUQ, hGdJj JJYdb HfXGe GdMce, hGdSdWGJ GdYGeI, heUGOQ GdbGfhf, hCge GdbhGYO GdbGfhfjI GdehVhYjI hGdELQGFjI, hebGQfI GdbhGYO GdbGfhfjI Hjf GdbGfhfjf, bGYOI HbGYOI, hfUG HfU, dcd aQY ef aQhY GdbGfhf GdYGe hGdNGU(B. (3hHjGf CSHGH hYhGed MOhK CKQ ddbGfhf GdaQfSj Ydi GdbGfhf GdeUQj Ch GeJfGY MOhKg, hGdfJGFL GdeJQJHI Ydi Pdc(B.s
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI, (B2021.s
(3HHdjhLQGajG(B: (3UaMGJ (B479-509.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdMedI GdaQfSjIs; (3CKQ GdbGfhf GdaQfSj Ydi GdbGfhf GdeUQjs; (3eUGOQ GdbGfhf NdGd GdYUQ GdYKeGfjs; (3GdbVGA NdGd GdYUQ GdYKeGfjs; (3GdbVGA NdGd YUQ GdeeGdjcs; (3bGfhf GdeQGaYGJ GdeOfjI hGdJLGQjI s; (3fXGe GdMce aj aQfSGs; (3GdbhGYO GdbGfhfjI GdELQGFjI aj eUQ s; (3bHjd GdMedI GdaQfSjIs; (3LjT GdMedI GdaQfSjIs; (3GdMedI GdaQfSjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- 2021